Bus protection (System protection technology)
The objective of this module is to review the different bus layouts that are used in power systems and to present the different protection schemes that are installed to protect against bus faults. Topics include: features of different bus arrangements such as single breaker-single bus, single buses connected with bus tie breaker, main and transfer buses with single breaker, single breaker-double bus, double breaker-double bus, ring bus and breaker-and-a-half bus. Partial differential protection with overcurrent relays, directional comparison schemes; residual current differential schemes and CT saturation problems.